Предмет: Алгебра,
автор: yuliyagl
lg (x^2 +2x-3)=lg (x-3)
Ответы
Автор ответа:
0
ОДЗ:
x² +2x -3 > 0 и x-3 > 0
(x-1)(x+3)>0 и x > 3
Общее одз: x > 3
x² +2x -3 = x - 3
x² +x = 0
x = 0; x = -1 // не удв. ОДЗ
Ответ: x∉∅
x² +2x -3 > 0 и x-3 > 0
(x-1)(x+3)>0 и x > 3
Общее одз: x > 3
x² +2x -3 = x - 3
x² +x = 0
x = 0; x = -1 // не удв. ОДЗ
Ответ: x∉∅
Похожие вопросы
Предмет: Биология,
автор: Polinashaldina
Предмет: История,
автор: itslodjik
Предмет: Литература,
автор: dinarastecuk
Предмет: Физика,
автор: Katika00
Предмет: Математика,
автор: пулатовалариса